Investigation of Magnesium–Sulfur Batteries using Electrochemical Impedance Spectroscopy. (1st April 2020) - Häcker, Joachim; Danner, Christian; Sievert, Brigitta; Biswas, Indro; Zhao-Karger, Zhirong; Wagner, Norbert; Friedrich, K. Andreas
Abstract: The present study aims to fundamentally understand the magnesium-sulfur battery and the interfacial processes involved. Therefore, electrochemical impedance spectroscopy (EIS) was carried out on symmetrical Mg/Mg and S/S cells as well as on full Mg/S cells. Besides the electrochemical behavior at the open-circuit voltage (OCV), the impedance evolution during the first discharge has been investigated at equidistant states of charge (SOC) and different temperatures. It was confirmed that sulfur species diffuse into the electrolyte, causing initial self-discharge and contributing to the solid electrolyte interphase (SEI) formation, even during the early stages of discharge. In fact, elevated temperatures further boost the self-discharge, but on the other hand significantly enhance the magnesium sulfide formation. Besides sulfur species, magnesium fluoride was found to be a main SEI component on both, anode and cathode side. According to these findings, equivalent circuit models (ECM) are proposed, indicating the formation of a high resistance passivation layer on the magnesium electrode as well as a rather slow cathodic charge transfer and sluggish MgS nucleation kinetics at the sulfur electrode. Graphical abstract: Image 1 Highlights: EIS applied to Mg/Mg, S/S and Mg/S cells during OCV and first discharge cycle. Magnesium surface layers exhibit large impedance at least in absence of polarization. Sulfur species contribute to SEI formation even in early stages of discharge. MgS nucleation kinetics, but also sulfur dissolution and consequent self-discharge boosted by temperature. Magnesium fluoride as SEI component present on both, anode and cathode side.